Optimal observation mode scheduling for systems under temporal constraints - Tesarova, E; Svorenova, M; Barnat, J; Cerna, I (American Automatic Control Council, 2016)
Modern control systems use various sensors to decrease the amount of uncertainty under which they operate. While providing observation of the current state of the system, sensors require resources such as energy, time and communication. We consider discrete models of such systems with non-deterministic control transitions and multiple observation modes that provide different information about the system’s states. We consider two control problems. First, we aim to construct a control and observation mode scheduling strategy that guarantees satisfaction of a finite-time temporal property given as a formula of syntactically co-safe fragment of LTL (scLTL) and at the same time, minimizes the worst-case cost associated with observation modes until the point of satisfaction. Second, the bounded version of the problem is considered, where the temporal property must be satisfied within given finite time bound. We present correct and optimal solutions to both problems and demonstrate their usability on a case study motivated by robotic applications.